Genetic inheritance of cytochrome P450-mediated metabolic resistance to chlorsulfuron in a multiple herbicide resistant Lolium rigidum population - Han, H. (2014)
Field evolved resistance to acetolactate synthase (ALS)-inhibiting herbicides in a multiple resistant Lolium rigidum population (VLR69) is known to be mainly due to enhanced rates of herbicide metabolism, likely involving cytochrome P450 monooxygenases. The present study investigates genetic inheritance of P450-mediated metabolic resistance to the ALS-inhibiting herbicide chlorsulfuron. To this end, a P450-mediated, metabolism-based resistant sub-set of VLR69 was carefully selected using plant vegetative cloning, appropriate herbicide screen test and the known P450 inhibitor malathion. Both intermediate and near-dominant nuclear-encoded phenotypic resistance traits were observed in 14 reciprocal F1 families. The segregation of phenotypic chlorsulfuron resistance in j-F2 families was analysed using genetic inheritance models involving one or two loci. The results from four j-F2 families revealed complex patterns of genetic inheritance of P450-mediated metabolic resistance in genetically diverse and cross-pollinated species L. rigidum: multiple loci are likely involved and interact with herbicide rates and environmental conditions in mediating the resistance phenotype.